Ablative fractional CO2 laser for burn scar reconstruction: An extensive subjective and objective short-term outcome analysis of a prospective treatment cohort. Issue 3 (May 2017) - Issler-Fisher, Andrea C.; Fisher, Oliver M.; Smialkowski, Ania O.; Li, Frank; van Schalkwyk, Constant P.; Haertsch, Peter; Maitz, Peter K.M.
Highlights: Extensive analysis of subjective and objectives outcomes of burn scars treated with ablative fractional laser resurfacing. Evaluation of pruritus and neuropathic pain before and 6 weeks after treatment with ablative fractional CO2 laser. First analysis of burns specific quality of life following treatment with ablative fractional CO2 laser. Abstract: Background: The introduction of ablative fractional CO2 lasers (CO2 -AFL) for burn scar management shows promising results. Whilst recent studies have focused on objective scar outcomes following CO2 -AFL treatment, to date no data on patient subjective factors such as quality of life are available. Methods: A prospective study was initiated to analyze the safety and efficacy of the CO2 -AFL. Various objective and subjective outcome parameters were prospectively collected from the date of first consultation and follow-up following treatment. Objective factors include the Vancouver Scar Scale (VSS), the Patient and Observer Scar Assessment Scale (POSAS), and ultrasound measurements of the thickness of the scar. Subjective parameters included the assessment of neuropathic pain and pruritus, as well as the evaluation of improvement of quality of life following CO2 -AFL with the Burns Specific Health Scale (BSHS-B). For treatment effect analysis, patients were stratified according to scar maturation status (> or <2 years after injury). Results: 47 patients with 118 burn scars completed at least one treatment cycle. At a median of 55 days (IQR 32–74) after CO2 -AFL treatment all analyzed objective parameters decreased significantly: intra-patient normalized scar thickness decreased from a median of 2.4 mm to 1.9 mm ( p  < 0.001) with a concomitant VSS-drop from a median of 7 to 6 ( p  < 0.001). The overall POSAS patient scale decreased from a median of 9 to 5 ( p  < 0.001) with similar effects documented in POSAS observer scales. Both pain and pruritus showed significant reduction. Quality of life increased significantly by 15 points (median 120 to 135; p  < 0.001). All of the identified changes following CO2 -AFL were equally significant irrespective of scar maturation status. Conclusion: Our preliminary results confirm significant improvement in thickness, texture, colour, and symptoms following treatment with CO2 -AFL. Foremost, quality of life of patients with both immature and mature scars (up to 23 years after injury) improved significantly after just one treatment session. To our knowledge, this is the first study to document such holistic treatment effects in burn patients treated by CO2 -AFL.